TINGKAT PENGETAHUAN MENGENAI KESEHATAN REPRODUKSI PADA REMAJA LAKI-LAKI DI SMP NEGERI KOTA JAMBI - Lisa Anita Sari (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Adolescence is a period of transition from children to adult marked by physical, emotional and psychological changes. Knowledge about health reproductive is very important for adolescent, in order to improve health behavior, avoid casual sex, and reduce the number of sexually transmitted infections. In the stages of adolescent development, there are major changes in the stages of adolescent development which cause adolescence to be relatively volatile compared to other developmental periods. The purpose of this study was to determine the level of knowledge of male adolescents about health reproductive at Junior High School at Kota Jambi in 2020. The research design was used descriptive quantitative study which conducted at Junior High School of 4, 6 and 17 at Jambi City from June to August 2020. The total sampling amount of 220 respondents who randomly selected by the simple random sampling method. The instrument was used the questionnaire that was modified by the researcher and also valid and reliable. Based on the research that has been done, it was found that statistically adolescents in Junior High School of 4, 6 and 17 at Jambi City had high level of knowledge on health reproductive (55.9%). Statistically, it was found that male adolescents had high level of knowledge. The efforts that can be made by health workers or nurses are to provide regular education to adolescents about health reproductive, so the adolescents get the correct understanding and avoid adverse effects of irregularities in health reproductive.